World Economic Trends: An Enquiry - Akhilesh Chandra Prabhakar (International Journal of Management Studies, 2013)
The series of current global economic and fi nancial crises especially in the USA and the European Stock Exchange Markets, the international division of labour and the global distribution of economic and political power led by free markets economies clearly indicate the collapse of Adam Smith’s ideology, and the Thatcher–Reagan free– market model that dominated thinking for 30 years has been discredited. A practical solution for the current ills is possible.